NEW APPROACHES TO SYNTHESIS OF HETEROPOLYNUCLEAR COMPLEXES (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
The idea of direct synthesis of coordination compounds — the use of elemental metals or their oxides as starting materials — has been developed into the “salt route,” “ammonium salt route,” “direct template synthesis,” and “direct permanganate” methods to synthesize heteropolynuclear complexes of transition metals. The advantages of this approach in obtaining heteropolynuclear complexes are shown by taking complexes of transition metals with aminoalcohol ligands, ethylenediamine, and their derivatives as examples. The results of the X-ray crystal structure analysis of the most interesting complexes are presented. The perspectives of the development of the direct synthesis methods for preparation of heteropolynuclear complexes are discussed.
Keywords: -